The spiritual search of the ideal of holiness in Paul Claudel’s mystery drama «L’Annonce faite `a Marie: Annunciation of the Virgin Mary» (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
The article investigates the role and place of the phenomenon of holiness as the pinnacle of spiritual search in Paul Claudel’s dramatic work «Annunciation of the Virgin Mary» and the means of adequately presenting this concept in Ukrainian translations. Paul Claudel’s dramatic aesthetics is closely linked to the Shakespearean dramatic concept, P.Calderon’s theatre, as well as to the foundations of ancient high tragedy by Aeschylus and Sophocles. As a playwright, Paul Claudel, a symbolist whose works see in the visible world a sign of hidden content, contributes to the development of the poetics of modern religious drama. The main lexical components that shape the concept of holiness are highlighted in this study so as torender their adequate translation into Ukrainian. The division in to micro-concepts that contribute to form the personality of the characters is here in suggested together with the essence of the concept by which the images are arranged in the drama. The paper also notes the position of the author who pays less attention to external factors. Characterization, which mainly occurs through replies, remarks and statements, conﬁrms the purpose of the study, i.e. that the ideal of holiness is formed in everyday actions for the sake of others. Paul Claudel’s work presents liturgical texts, prayers and songs, full of biblical symbols, which is the second subtext layer: the liturgical and that’swhytheworkhasamonumentalcharacternd that’swhytheworkhasamonumentalcharacter.
Keywords: holiness; drama-mystery; Catholic Renaissance; total theatre; Symbolism; concept; style; genre; mentality; symbol